Factors affecting RIG-I-Like receptors activation - New research direction for viral hemorrhagic fevers - Małkowska, Paulina; Niedźwiedzka-Rystwej, Paulina (Frontiers in Immunology, 2022)
Viral hemorrhagic fever (VHF) is a term referring to a group of life-threatening infections caused by several virus families (Arenaviridae, Bunyaviridae, Filoviridae and Flaviviridae). Depending on the virus, the infection can be mild, and can be also characterized by an acute course with fever accompanied by hypervolemia and coagulopathy, resulting in bleeding and shock. It has been suggested that the course of the disease is strongly influenced by the activation of signaling pathways leading to RIG-I-like receptor-dependent interferon production. RIG-I-like receptors (RLRs) are one of two major receptor families that detect a viral nucleic acid. The activation of RLR receptors is influenced by many factors, including autophagy, which also appears to have a key role in the antiviral immune response in VHF. In the present study, we collected data on RLR receptors in viral hemorrhagic fevers and described factors that may influence the activation of the antiviral response. RLR receptors seem to be a good target for VHF research, which may contribute to better therapeutic and diagnostic strategies. However, due to the difficulty of conducting such studies in humans, we suggest using an animal model - Lagovirus europaeus.